MANAJEMEN PEMBELAJARAN KIMIA MODEL DIRECT INSTRUCTION DISERTAI DISKUSI PADA SISWA MA - Yunitasari Yunitasari Yunitasari (UNIVERSITAS BENGKULU, 2016)
This study aims to: improve the quality of the learning process chemistry and enhance students' understanding through learning management chemical model of direct instruction. Thisresearch is a class act. Subjects were students in grade XI MA Negeri 2 Bengkulu City. The data collection is done by means of written tests, observations, questionnaires and interviews . Analysis of the data consists of data reduction , data presentation, drawing conclusions / verification . Theresults of this study indicate that: (1) learning management direct instruction with discussion can improve the quality of the learning process chemicals , (2) learning management direct instruction with discussion to increase understanding of chemical concepts. It can be seen through the increase in the average value of students from the initial test (1.83), the test cycle I (4.99) and test cycle II (7.03).Keywords: management, learning, direct instruction, discuss